GeoBoids: A Mobile AR Application for Exergaming - Lindeman, R. W.; Lee, G.; Beattie, L.; Gamper, H.; Pathinarupothi, R.; Akhilesh, A.; Gamper, Hannes (Proc. Int. Symp. Mixed and Augmented Reality (ISMAR), 2012)
We have designed a mobile Augmented Reality (AR) game which incorporates video see-through and spatialized audio AR techniques and encourages player movement in the real world. In the game, called GeoBoids, the player is surrounded by flocks of virtual creatures that are visible and audible through mobile AR application. The goal is for the player to run to the location of a GeoBoid swarm in the real world, capture all the creatures there, then run to the next swarm and repeat, before time runs out, encouraging the player to exercise during game play. The most novel elements of the game are the use of audio input and output for interacting with the creatures. The interface design of the game includes AR visualization, spatialized audio, touch gestures and whistle interaction. Feedback from users in a preliminary user study was mostly positive on overall game play and the design of the UI, while the results also revealed improvements were needed for whistle interaction and the visual design of the GeoBoids.